A Treatise on Navigation by Steam Comprising a History of the Steam Engine - Ross, John (Cambridge library collection. Technology, 1828)
Following distinguished service during the Napoleonic Wars, the Scottish naval officer and Arctic explorer Sir John Ross (1777-1856) embarked on an abortive expedition to discover the North-West Passage. The existence of the Croker mountains, which he claimed had blocked his path, was afterwards disputed and his reputation suffered. His 1819 account of that voyage has been reissued in the Cambridge Library Collection. Prior to setting out in a steam vessel on a second expedition, for which he would be knighted, Ross published the present work in 1828. Seeking to establish himself as an authority on steam power when the technology was still in its infancy, Ross explores the development of the steam engine, the commercial and military potential of steam navigation, and how this called for a radical change in naval tactics. Illustrated throughout, this is the work of a practical maritime mind, combining both historical and technical detail.